1984
DOI: 10.1111/j.1365-2672.1984.tb02361.x
|View full text |Cite
|
Sign up to set email alerts
|

Soft rot Erwinia bacteria in surface and underground waters in southern Scotland and in Colorado, United States

Abstract: An anaerobic liquid enrichment method followed by plating on a selective medium revealed that the soft rot coliform bacterium Erwinia carotovora subsp. carotovora was generally present in water from drains, ditches, streams, rivers and lakes (including reservoirs) in southern Scotland and in Colorado, United States, in mountainous, upland and arable areas through the year. Many sites were remote from susceptible or diseased crops. Erwinia carotovora subsp. atroseptica was isolated much less frequently and no E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 17 publications
1
28
1
Order By: Relevance
“…Dickeya chrysanthemi (formerly Erwinia chrysanthemi) is thought to be a part of the indigenous microorganisms on weeds and in sediments in alpine streams in Australia (Cother and Gilbert, 1990). Numerous studies illustrated that Pectobacterium carotovorum (formerly E. carotovora) is present in a wide range of surface and underground waters including those used in irrigation (McCarter-Zorner et al, 1984;Harrison et al, 1987). Franc (1988) further revealed that this bacterium was present in at least 80% of samples of ocean water and rainwater collected on the west coast of the United States and in samples of aerosols along the coast.…”
Section: Discussionmentioning
confidence: 99%
“…Dickeya chrysanthemi (formerly Erwinia chrysanthemi) is thought to be a part of the indigenous microorganisms on weeds and in sediments in alpine streams in Australia (Cother and Gilbert, 1990). Numerous studies illustrated that Pectobacterium carotovorum (formerly E. carotovora) is present in a wide range of surface and underground waters including those used in irrigation (McCarter-Zorner et al, 1984;Harrison et al, 1987). Franc (1988) further revealed that this bacterium was present in at least 80% of samples of ocean water and rainwater collected on the west coast of the United States and in samples of aerosols along the coast.…”
Section: Discussionmentioning
confidence: 99%
“…Ralstonia solanacearum was reported to persist in surface water in portions of Florida (13) and Egypt (5). Species of Erwinia causing soft rot of potato were discovered in surface and below-ground waters in both Colorado and Scotland (2,18). Species of Xanthomonas (6) and Pseudomonas (19) were isolated from surface waters as well.…”
Section: Irrigation Of Tomato Plants (Lycopersicon Lycopersicum)mentioning
confidence: 99%
“…SRE were recovered from approximately 60% of all water samples collected. McCarter-Zorner et al (1984) found that Eee was generally present in water in southern Scotland and Colorado, U.S. in mountainous, upland, and arable areas throughout the year, even in sites remote from potato fields. However, not all SGs from soil, tuber, and water were associated with stem infections.…”
Section: Discussionmentioning
confidence: 96%
“…Cother (1979) found that the soil-borne population appeared to be more important than the seed tuber population in initiating seed tuber rotting in soil in New South Wales, Australia. More recently, water samples obtained from drains, ditches, streams, rivers, and lakes in southern Scotland and in Colorado, U.S. have been found to contain E. carotovora and it has been hypothesised that water may also be an inoculum source (McCarter-Zorner et al 1984). Other sources that have been implicated include the rhizosphere of susceptible and non-susceptible plants (McCarterZorner et al 1982), aerosols (Graham & Harrison 1975) and insects carrying the pathogen (Harrison et al 1977).…”
Section: Introductionmentioning
confidence: 99%